Clinical Physical Therapy - Suzuki, Toshiaki (IntechOpen, 2017)
Physical therapy services may be provided alongside or in conjunction with other medical services. They are performed by physical therapists (known as physiotherapists in many countries) with the help of other medical professionals. This book consists of 11 chapters written by several professionals from different parts of the world. It includes different kinds of chapters for clinical physical therapy with precious points for physical therapy, physical therapy for cancer, chronic venous disease, mental health, and other topics. We hope that the information provided in this book will instruct global physical therapists and related professionals.